PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) PADA MATERI POKOK EUBACTERIA BERBASIS PENDEKATAN ILMIAH - Almira Velda Harahap; Zulkifli Simatupang; Eni Susanti (Jurnal Pelita Pendidikan, 2017)
This research aims to know the value of a student worksheet Eubacteria based on scientific approach by experts and practitioners. This research has develop with 4-D models that has been modified consist three stages. The first stages is define, which include analysis of main competency, basic competencies, indicators of competence, and condition of student. The second stage is the design, which consist of data collection in the form of the syllabus, to formulate specific objectives to be achieved, preparing presentation framework. The third stage is develop, which consist of validation by matter expert and education expert, biology teacher responses, and student responses in a small group. The product produced in the form of worksheets Eubacteria based on scientific approach. Student worksheet complied and considered feasible by validation team. Results of the assesment team of matter expert showed an average 93,75% categorized a very good and education expert 92% categorized as very good. Result responses biology teacher got the result 80,21% categorized good. Result of student responses of the small group got 92% categorized as very good.Keywords : Development, Scientific Approach, Worksheet